Analysis Of The Influence Of Land Area, Number Of Producers, Production Costs On The Income Of Rice Farmers In Talunombo Village, Baturetno District, Wonogiri Regency - Pamungkas, Bagus Aditya Wahyu; Arif, Muhammad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The growth rate of the agricultural sector in Wongiri Regency over the last five years has decreased due to several factors that have caused changes in farmers' income. This research aims to determine the effect of land area, production amount, production costs on farmers' income. This research uses quantitative data obtained through a survey of farmers in Talunombo Village. Testing is carried out by carrying out classical assumption tests, multiple regression tests, and hypothesis tests. The results of this research show that the variable area and farmer income have a negative relationship. There is a probability value of 0.0049 which shows that land area has an effect on rice farmers' income. The variables total product and farmer income have a positive relationship. There is a probability value of 0.0000 which can be interpreted as the total product having an effect on rice farmers' income. The variable costs and farmer income have a positive relationship. There is a probability value of 0.0002 which indicates that production costs influence the income of rice farmers. To increase farmers' income, maximum management is needed, such as providing good land and allocating appropriate production costs to increase production results.